Eksplorasi Determinan Finansial Terhadap Profitabilitas: Pendekatan Kuantitatif Pada Emiten Sektor Industri Di Pasar Modal Indonesia - Sisca Contesa; Theresia Contesa (Publikasi Indonesia, 2025)
This study aims to analyze the influence of working capital turnover, liquidity, and sales growth on profitability in industrial sector companies listed on the Indonesia Stock Exchange (IDX). The sample selection was carried out using the purposive sampling method, so that 35 companies were obtained as an analysis unit. This study uses secondary data obtained from the official website of the Indonesia Stock Exchange, with a specific observation period. The data analysis technique used is multiple linear regression, with the help of IBM SPSS software version 22. The results of the analysis show that working capital turnover, liquidity, and sales growth simultaneously and partially have a significant positive influence on the company's profitability. These findings indicate that efficiency in working capital management, healthy liquidity levels, and increased sales are important factors in driving the company's financial performance in the industrial sector.